DIFFERENCES BETWEEN INTROVERT AND EXTROVERT PERSONALITY ON DEPRESSION LEVEL IN STUDENTS OF MEDICAL EDUCATION PROGRAMS FACULTY OF MEDICINE 2017 TANJUNGPURA UNIVERSITY - Ryan Pratama Safitra (Jurnal Nasional Ilmu Kesehatan, 2021)
Depression is a psychiatric disorder that affects the mood of a person, it can affect their daily life due to the feelings of deep sadness. One of the triggers of depression is personality. Personality can be divided into introvert and extrovert personality based on their interaction. The purpose of this study is to know the differences between introvert and extrovert personality on depression level in students of medical education programs faculty of medicine 2017 Tanjungpura University.The type of this research is an observational analytical research with Cross Sectional approach. A total of 34 students was involved in this experiment. Beck Depression Inventory II and Eysenck Personality Inventory-A questionnaire was used as measuring instrument. The results is respondents who have introvert personality and do not have depression symptoms (normal) are 3 people (8.8%), while respondents who have introvert personality and have depression symptoms are 13 people (38.3%). Then respondents who have extrovert personality and do not have depression symptoms (normal) are 13 people (38.2%), while respondents who have extrovert personality and have depression symptoms are 5 people (14.7%). Based on statistical tests showed p value <0.05. The conclusion in this research is there is differences between introvert and extrovert personality on depression level in students of medical education programs faculty of medicine 2017 Tanjungpura University.